Evolution of Academic Literature on Tax Regulation: A Bibliometric Approach 2015-2025 - Sopriyanti, Mita; Santoso, Rachmat Agus; Fitriana, Fitriana (Goodwood Akuntansi dan Auditing Reviu, 2025)
Purpose: This research aims to trace the development of literature related to tax regulations in various countries including articles published from 2015 to 2025 using bibliometric methods based on the analysis of Co-occurrence units All keywords, Bibliographic coupling unit country and documents. Methodology/approach: Bibliometric analysis methodology was conducted on 191 articles between 1976 and 2025. Data was obtained from Scopus meta data which was then analyzed using Vosviewer. Results/findings: In conclusion, the topic of "taxation" is most frequently discussed in academic articles. Indonesia is the country most involved in research on tax regulations. Furthermore, Ormeno-Perez's (2023) paper shares the most references with other papers, although it remains under-cited. Conclusion: The study reveals that “Taxation” dominates bibliometric research from 1976–2025, with Indonesia showing the strongest research linkage. These findings enrich taxation literature and highlight opportunities for further exploration of themes such as digital taxation, tax compliance, and tax justice. Limitations: Collaboration between researchers is still limited, meaning that there has not been much cooperation between authors on this topic. Some new documents have also not had much influence because they have not been published for a long time. In addition, this study only focuses on certain keywords, so there may be other tax topics that have not been covered. Contribution: This research helps map the development of tax studies during 2015–2025. The results can be a reference for further research, especially for those who want to explore new themes. This study also encouraged other researchers to collaborate more and expand tax research topics.